ANALISIS DAMPAK DAN FAKTOR TERJADINYA KEKERASAN DALAM RUMAH TANGGA DI DESA CILILIN - Ageng saepudin kanda S; Herawati (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Abstrak. Violence against women, both inside and outside the household, which was previously considered a myth and a personal problem, has now become a reality in community and household life in the reform era. Domestic violence has special characteristics, especially related to the relationship between the perpetrator and the victim, whether in a familial context or an employer-domestic servant relationship. Therefore, this research was conducted to find out what impacts and factors cause domestic violence and to find out what the impacts are after domestic violence occurs. This research uses qualitative research methods, involving descriptive approaches and case studies. Research is focused on individual circumstances holistically, without reducing it to variables or hypotheses first. The results obtained in this research are that marriages that are not old enough are one of the causes of domestic violence because they are still young and cannot control their emotional nature. Furthermore, additional family income also plays a role in the occurrence of Domestic Violence (KDRT). Keywords: Violence, Domestic, Community, Family